Okay, here we have this:
We need to graph the following equation by first finding its x- and y-intercepts:
x-intercept:
![\begin{gathered} -(2)/(3)x+3=0 \\ -(2)/(3)x=-3 \\ -2x=-9 \\ x=(9)/(2)=4.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8gek6n2fhlh4kgic6o56cgt7lkyc439aqt.png)
Here we obtain that the x-intercept is (4.5, 0).
y-intercept:
![\begin{gathered} y=-(2)/(3)\cdot\: 0+3 \\ y=-0+3 \\ y=3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9pyoj9tkrmzyw5z1iy9797dvqoe66ptjum.png)
Here we obtain that the y-intercept is (0, 3).
Now, let's graph this: